2015
DOI: 10.1597/14-050
|View full text |Cite
|
Sign up to set email alerts
|

Parent-Reported Family Functioning among Children with Cleft Lip/Palate

Abstract: Objective To examine family functioning related to sociodemographic and clinical characteristics in youth with cleft lip and/or palate (CL/P). Design Cross-sectional, multisite investigation. Setting Six U.S. cleft centers. Patients/Participants A diverse sample of 1200 children with CL/P and their parents. Main Outcome Measure Parents completed the Family Environment Scale (FES), which assesses three domains of family functioning: cohesion (or closeness), expressiveness (open expression of feelings), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 49 publications
(82 reference statements)
3
17
0
Order By: Relevance
“…Nonetheless, two studies reported CL/P to have a negative impact on family life (Kramer et al, 2009;Gkantidis et al, in press). Ethnicity was also associated with greater family cohesion in one study (Crerand et al, 2015).…”
Section: Parent-child Relationshipsmentioning
confidence: 88%
See 1 more Smart Citation
“…Nonetheless, two studies reported CL/P to have a negative impact on family life (Kramer et al, 2009;Gkantidis et al, in press). Ethnicity was also associated with greater family cohesion in one study (Crerand et al, 2015).…”
Section: Parent-child Relationshipsmentioning
confidence: 88%
“…Similarly, children with CL/P were found to demonstrate more autonomous behaviour and to interrupt their parent less frequently (Gassling, Christoph et al, 2014). According to self-reports, individuals with CL/P described normal or particularly close relationships with family members (Cheung et al, 2006;Gussy & Kilpatrick, 2006;Oosterkamp et al, 2007;Chimruang et al, 2011;Crerand et al, 2015;Gkantidis et al, in press), which was believed to act as a buffer against Downloaded by [Library Services, University of the West of England] at 07:02 08 February 2016 social challenges (Hall, Gibson, James & Rodd, 2013;Tiemens et al, 2013;Stock, Feragen et al, in press). Nonetheless, two studies reported CL/P to have a negative impact on family life (Kramer et al, 2009;Gkantidis et al, in press).…”
Section: Parent-child Relationshipsmentioning
confidence: 99%
“… 1 (Rief, Nanke, Klaiberg, & Braehler, 2004) 2 (Lowe et al, 2008) 3 (Reitman, Currier, & Stickle, 2002) 4 (Crerand et al, 2014) 5 (University of Wisconsin & Maccubbin, 1987) 6 (Glaesmer et al, 2012) …”
Section: Figurementioning
confidence: 99%
“…This study also examined family functioning with the Family Environment Scale. While family functioning was within the normal range, specific areas (e.g., race, ethnicity, type of insurance, and clinical need) were related to 2 domains of family functioning: cohesion (commitment and support within families) and expressiveness (expression of feelings within families; Crerand et al 2015). Specifically, non-Hispanic and/or White families and those with private insurance reported greater cohesion and expressiveness than African American and Latino families and those with public insurance, respectively.…”
Section: Cross-sectional Findingsmentioning
confidence: 99%